Devising Uterine Involution Score Card for Assessment of Postpartum Uterine Remodeling in Dystocia Affected Buffaloes - Gulia, Nakul; Honparkhe, Mrigank; Bisla, Amarjeet; Kumar Singh, Ashwani; Singh , Prahlad (The Indian Journal of Animal Reproduction, 2025)
The future fertility of the postpartum buffalo depends upon healthy peri-partum period subsequently leading to timely uterine involution and lesser development of uterine infections. Dystocia is one of the most important obstetrical con ditions, and requires immediate attention of the veterinarians, to prevent severe economic losses to the farmers arising from postpartum complications. The present study was planned with objective to design a score card for assessing uter ine involution in dystocia affected buffaloes and its validation. The score card was based on six parameters (location of uterus, diameter of cervix, uterine body, gravid and non-gravid uterine horns, and presence of types of uterine fluid) which were evaluated by the per-rectal and USG examination. Uterine torsion was found to be the most common cause of dystocia (50.00%; 15/30) followed by feto-maternal disproportion (20.00%; 6/30), fetal mal-dispositions (20.00%; 6/30) and fetal monstrosity (10.00%; 3/30), respectively. The average uterine involution score on day 20, 45 as well as combined score of all animals and speed of uterine involution was assessed. It was observed that 36.67% animals had delayed uterine involution indicating negative impact of dystocia on uterine health. So, it was concluded that devised uterine involution scorecard in this study could be beneficial for assessment of speed as well as extent of uterine involu tion in dystocia affected animals.